Profiling of cytosolic and mitochondrial H2O2 production using the H2O2-sensitive protein HyPer in LPS-induced microglia cells. (27th July 2017) - Park, Junghyung; Lee, Seunghoon; Lee, Hyun-Shik; Lee, Sang-Rae; Lee, Dong-Seok
Highlights: Subcellular H2 O2 formation was confirmed using the HyPer in BV-2 microglia. Cytosolic H2 O2 started increasing constantly from early time in response to LPS. Mitochondrial H2 O2 rapidly increased at later time by LPS treatment. MAPK, such as JNK and p38 affected cytosolic H2 O2, but not mitochondrial H2 O2 . Abstract: Dysregulation of the production of pro-inflammatory mediators in microglia exacerbates the pathologic process of neurodegenerative disease. ROS actively affect microglia activation by regulating transcription factors that control the expression of pro-inflammatory genes. However, accurate information regarding the function of ROS in different subcellular organelles has not yet been established. Here, we analyzed the pattern of cytosolic and mitochondrial H2 O2 formation in LPS-activated BV-2 microglia using the H2 O2- sensitive protein HyPer targeted to specific subcellular compartments. Our results show that from an early time, cytosolic H2 O2 started increasing constantly, whereas mitochondrial H2 O2 rapidly increased later. In addition, we found that MAPK affected cytosolic H2 O2, but not mitochondrial H2 O2 . Consequently, our study provides the basic information about subcellular H2 O2 generation in activated microglia, and a useful tool for investigating molecular targets that can modulate neuroinflammatory responses.